Higher-order QCD in Higgs to gluon gluon - Nogueira, Guilherme de Araújo (2024)
One of the most prominent decay channels of the Higgs boson is the decay of the Higgs into two gluons. The decay width ⌈(h → gg) starts at second order in the strong coupling αs and is known up to Ο(α6s) in perturbative QCD. However, the truncation error of this quantity needs to be investigated, considering that its precise theoretical knowledge is part of crucial tests of the Standard Model of particle physics. In order to achieve better control over this truncation error, it is necessary to know the coefficients at higher order. In this work, we produce accurate estimates for the first unknown coefficient of the Higgs decay into two gluons, at Ο(α7s). We investigate the coefficients at high orders using rational approximants also known as Padé approximants, in combination with the Borel transform of the series, in addition to employing other methods such as the so-called Dlog Padés, renormalization scheme variation, and conformal mapping. We provide model-independent estimates for the first unknown coefficient, c5, in the series for the Higgs decay into two gluons. We analyzed two prescriptions for the renormalization of the top-quark mass, considering the dependence on the number of flavors of light quarks, denoted as nf . For the case of greatest interest, with nf = 5, we obtained estimates of c5 = 304±106 under the Scale Invariant prescription, and c5 = -293 ± 78 for the On-Shell top-quark mass. This allows us to assess the intrinsic truncation uncertainty of this quantity in light of our results.